2018
DOI: 10.1111/cla.12365
|View full text |Cite
|
Sign up to set email alerts
|

Penicillium section Lanata‐divaricata from acidic soil

Abstract: Penicillium species in section Lanata-divaricata are common soil-inhabiting fungi, but their presence in acidic soil has rarely been investigated. In an ongoing survey of Penicillium species occurring in China, 465 strains were isolated from soil, and of which 60 belonged to section Lanata-divaricata. The majority of these strains were isolated from acidic soil. The phylogenetic relationship between these 60 isolates and accepted species of section Lanata-divaricata was studied using ITS, BenA, CaM and RPB2 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…Notes : Species of Penicillium in the section Lanata-Divaricata are characterized by divaricate conidiophores and broadly scattering colonies ( Houbraken and Samson, 2011 ). Members of Penicillium are widespread in food products, soil, plant-decaying materials, animals and indoor environments ( Visagie et al, 2016 ; Diao et al, 2018 ; Heo et al, 2019 ). Many recent studies reported Penicillium strains belonging to the section Lanata-Divaricata ( Visagie et al, 2016 ; Lorenzini et al, 2019 ; Hyde et al, 2019a ; Guevara-Suarez et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notes : Species of Penicillium in the section Lanata-Divaricata are characterized by divaricate conidiophores and broadly scattering colonies ( Houbraken and Samson, 2011 ). Members of Penicillium are widespread in food products, soil, plant-decaying materials, animals and indoor environments ( Visagie et al, 2016 ; Diao et al, 2018 ; Heo et al, 2019 ). Many recent studies reported Penicillium strains belonging to the section Lanata-Divaricata ( Visagie et al, 2016 ; Lorenzini et al, 2019 ; Hyde et al, 2019a ; Guevara-Suarez et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“… Crous et al (2018) established Penicillium guaibinense from soil in the Guaibim sandbank in Bahia, Brazil. Diao et al (2018) introduced P. austrosinense from acidic soil in Hainan, China. The conidia of P. guaibinense (CCDCA 11512 = 23EM8: ex-type) are finely rough and broadly subglobose, whereas they are smooth-walled and globose to ellipsoidal in P. austrosinense (CGMCC 3.18797: ex-type); despite this, conidial sizes between P. guaibinense and P. austrosinense are slightly similar [2–3 × 2–3 μm (av.…”
Section: Resultsmentioning
confidence: 99%
“…The results presented in this study were obtained through the combination of morphological and molecular data, whose phylogenetic analyses indicated the presence of three Penicillium species (P. brasilianum, P. cluniae, and P. echinulonalgiovense) in the Lanata-Divaricata section, being reported as endophytes for the first time. The Penicillium section Lanata-Divaricata comprises of around 75 species, and some authors have described the representatives of this section as divaricate with subterminal to terminal metulae, in intercalary positions (associated with monoverticilate conidiophores), with the members being highly similar to each other and also capable of displaying variations within the same species Visagie et al 2015;Barbosa et al 2018;Diao et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analyses. β-tubulin and calmodulin sequences were chosen based on published literatures (Barbosa et al 2018;Diao et al 2018;Kubátová et al 2019) and included in the matrix along with the endophytic Penicillium sequences of this study. Sequences were aligned using MAFFT v.7 (Katoh and Standley 2013) and manually improved in MEGA v. 7 (Kumar et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…This genus is subdivided into two subgenera (Aspergilloides and Penicillium) and 26 sections [1,22]. Species of Penicillium can be isolated from different environmental sources including air, soil, indoor environments, and food products [1,23]. Penicillium species are also identified in a manner similar to Aspergillus species, through the use of morphological characteristics, multi-locus DNA sequencing, and extrolite analyses.…”
Section: Introductionmentioning
confidence: 99%